DESIGN OF A MULTIPLE FINGER PROSTHETIC HAND WITH A PASSIVE ADAPTIVE GRASP SYSTEM - Bhatti, Shameem (My University, 2010)
Hand amputation is an extremely traumatic experience for a patient; it has been observed that patients that experience the loss of a limb have developed mental and emotional disorders. In order to improve the overall quality of life for hand amputee patients, a number of prosthetic devices are available on the market today. Many of these devices fail to approach the level of dexterity possible of the human hand. Presented in this paper is the design of a prosthetic hand prototype that attempts to duplicate some of the high dexterity of the human hand. Using an adaptive grasp system and an innovative finger link design, the natural appearance and motion characteristic of the human hand were modeled as closely as possible. Coupling this prosthetic prototype to an electromyogram setup and muscle signal classification software, it is our hope that we can control the prosthetic hand using the remaining muscles in the forearm. Enabling a more seamless transition and rehabilitation for hand amputee patients; effectively improving their overall quality of life and mental state.
Keywords: Biomedical; Electrical and Computer Engineering; Biomedical